1973
DOI: 10.1002/jez.1401830105
|View full text |Cite
|
Sign up to set email alerts
|

Response of the toad, Xenopus laevis, to circulating antigens. II. Responses after splenectomy

Abstract: It was demonstrated that the spleen cannot be the only site of antibody induction or formation in Xenopus laevis -even though cellular activity in response to circulating antigen is most evident in this organsince serum antibody titres in splenectomized toads were comparable with those in sham-operated animals after immunization with human gamma globulin (in adjuvant) or with sheep erythrocytes. This is of interest since the spleen appears to be the only lymphoid organ in X . laevis with any complexity of stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In contrast to mammals, Xenopus splenic T cells are located in the red pulp area surrounding the white pulp (6). Most of the T cells are believed to be educated in the thymus since thymectomy, but not splenectomy, has a major effect on immune responsiveness (7). In Xenopus, the thymus anlagen arise around day 3 after fertilization at NF-stage 40 according to the Normal Table of Nieuwkoop and Faber (8).…”
Section: Xenopus Immune Cellsmentioning
confidence: 99%
“…In contrast to mammals, Xenopus splenic T cells are located in the red pulp area surrounding the white pulp (6). Most of the T cells are believed to be educated in the thymus since thymectomy, but not splenectomy, has a major effect on immune responsiveness (7). In Xenopus, the thymus anlagen arise around day 3 after fertilization at NF-stage 40 according to the Normal Table of Nieuwkoop and Faber (8).…”
Section: Xenopus Immune Cellsmentioning
confidence: 99%
“…In both tumours and granulomas, the main sites involved, in addition to the spleen, are the liver and kidney. The blood vessel involvement we noted as a feature of granuloma development (its with Turner's suggestion [25] that the liver and kidney sinuses might provide a site where lymphoid cells could cluster and respond to the presence of antigen.…”
Section: Immunological Aspectsmentioning
confidence: 94%
“…Noting the dearth of plasma cells in the spleens of normal or immunized Xenopus, they suggested that either Xenopus produce good antibody titres without the pro duction of typical plasma cells, or the proliferation response occurs in the spleen, followed by migration and subsequent differentiation elsewhere in the body. Turner [25] demonstrated that the spleen cannot be the only site of antibody production in Xenopus, as serum antibody titres in response to HGG and SRBC injection were as high in splenectomized toads as in shamsplenectomized toads. Thus, although the spleen is the only lymphoid organ in Xenopus which shows any complexity of structural organization, foci in other parts of the body (gut.…”
Section: Immunological Aspectsmentioning
confidence: 99%